591 Can 670Nm Red Light Protect Against Retinopathy of Prematurity and Reduce Lung Injury in a Neonatal Animal Model?. (October 2012) - Natoli, R; Valter, K; Barbosa, M; Dahlstrom, JE; Provis, J; Kent, AL
Abstract : Background: Retinopathy of prematurity is a vasoproliferative disorder that can cause blindness and adverse visual outcomes in extremely premature neonates. Red light at 670nm wavelength promotes cellular differentiation, proliferation and wound repair. Aims: To determine whether 670nm light promotes normal retinal vessel development in a mouse model of Oxygen Induced Retinopathy of Prematurity (OIR) and whether it would affect organ development and growth. Methods: Four groups of C57BL/6J mice were used: 1) Control; 2) OIR - 75% oxygen p7–12 days and normoxia p12–17 days; 3) OIR and 670nm light - 9 J/cm 2 daily from p7–17; 4) 670nm light - 9 J/cm 2 daily from p7–17. At p17 animals were sacrificed and retinal vasculature labelled with Lectin. Neovascularisation and vaso-obliteration were analysed using established protocols. Weight and length measurements were taken daily until the animals were sacrificed and all organs were harvested, weighed and examined macro- and microscopically. Results: Neovascularisation was significantly reduced in the 670nm treated OIR group (P<0.05). The 670nm treated mice had increased body weight from p13 but no change in length. The OIR+670nm mice had reduced alveolar haemorrhage in comparison to the OIR only mice (p<0.05). Conclusions: Exposure to 670nm red light appears to promote normal retinal vessel development and may protect against ROP. 670nm treatment may also reduce oxygen induced lung injury.